The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acs.jmedchem.6b00188
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Epothilone Binding Site on β-Tubulin by Photoaffinity Labeling: Identification of β-Tubulin Peptides TARGSQQY and TSRGSQQY as Targets of an Epothilone Photoprobe for Polymerized Tubulin

Abstract: Photoaffinity labeling with an epothilone A photoprobe led to the identification of the β-tubulin peptides TARGSQQY and TSRGSQQY as targets of the photoprobe for polymerized tubulin. These peptides represent residues 274–281 in different β-tubulin isotypes. Placing the carbene producing 21-diazo/triazolo moiety of the photoprobe in the vicinity of the TARGSQQY peptide in a homology model of TBB3 predicted a binding pose and conformation of the photoprobe that are very similar to the ones reported for 1) the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…The final major category of tubulin inhibitors is colchicine binding site agents. Colchicine (17), from the meadow saffron Colchicum autumnale L., was the first agent discovered in this group as a tubulin depolymerizing agent. The colchicine binding domain is located at the interface between the α and β tubulin dimer.…”
Section: Colchicine Binding Site Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final major category of tubulin inhibitors is colchicine binding site agents. Colchicine (17), from the meadow saffron Colchicum autumnale L., was the first agent discovered in this group as a tubulin depolymerizing agent. The colchicine binding domain is located at the interface between the α and β tubulin dimer.…”
Section: Colchicine Binding Site Agentsmentioning
confidence: 99%
“…Stabilizing agents are able to promote polymeric tubulin structures even when the unfavorable GDP molecule is bound and are more effective than endogenous MT‐associated proteins at stabilizing the MT . There are several drug categories within this class, including taxanes, epothilones, and laulimalide binding site agents . Representative drugs in this class can be found in Figure A.…”
Section: Introductionmentioning
confidence: 99%
“…Epothilones ( Figure 14 ), which belong also to the microtubule inhibitors, are macrocyclic compounds isolated from the bacterium Sorangium cellulosum based on the 16-membered lactone ring. Six major epothilones, EpoA–EpoF, and more than thirty other related compounds have been identified, so far [ 121 , 122 ]. EpoA ( 13a , Figure 14 ) and EpoB ( 13b , Figure 14 ) are bacterial natural products, while EpoC ( 13e , Figure 14 ) and EpoD ( 13f Figure 14 ), which were discovered later, are their precursors and lack the epoxide group [ 123 ].…”
Section: Microtubule Inhibitorsmentioning
confidence: 99%
“…Their main advantage when compared to compound 9 is enhanced water solubility, which is thirty times higher than that of taxanes, and also efficacy against taxane-resistant tumors [ 124 ]. The epothilone binding site in tubulin significantly overlaps the taxane binding site, therefore, epothilones compete in tubulin binding with compound 9 [ 121 , 125 ].…”
Section: Microtubule Inhibitorsmentioning
confidence: 99%
“…We also analyzed the binding pocket of both epothilone and 2l on beta-tubulin and found that there were 12 residues which are common to both 2l and epothilone (Table 5) showing that 2l and epothilone share the same binding pocket. Since the taxol binding pocket has hydrophobic residues in the H7 helix, M loop and β strand of S7, S9-10 ( Ranade et al, 2016), it is possible that 2l also makes some hydrophobic interactions within the binding pocket.…”
Section: Determination Of Binding Site Of 35-bis(styryl)pyrazole 2l mentioning
confidence: 99%